Rancang Bangun Sistem Informasi E-Learning di SMK Pasundan Rancaekek - Rohman, Rohman; Atmoko, Dwi (Jurnal Dimamu, 2024)
The design of an E-Learning information system is a system created to solve the problems being faced by SMK Pasundan Rancaekek in teaching and learning activities offline or face to face in front of the class. At least there are several problems that often occur during teaching and learning activities using the lecture method or explaining material in front of the class. So that it can cause some students to feel bored and some even fall asleep in class, besides that some students who can't go to school that day will miss the material, apart from students, the offline method can also have an impact on students if the teacher is unable to attend, so that the material on that day can't be delivered. The system development used in this research is OOAD (Object oriented analysis design) with the RUP (Rational unified process) model. And the system modeling tools it uses are UML (Unified Modeling Language) with the tools used are Use Case Diagrams, Class Diagrams, Activity Diagrams, and Sequence Diagrams. The results showed that With the design of this E-Learning information system, it is hoped that it can help solve the problems being faced by teachers and students at Pasundan Rancaekek Vocational School and teaching and learning activities can become more interesting and students who learn do not feel bored.